2015
DOI: 10.2967/jnumed.115.159384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recent Change in the National Institute of Standards and Technology Standard for 18F on the Relative Response of 68Ge-Based Mock Syringe Dose Calibrator Standards

Abstract: As a result of a recent change in the National Institute of Standards and Technology (NIST) activity standard for 18 F, we have determined new relative response ratios for a 68 Ge solid epoxy mock syringe source used in activity calibrators as a long-lived substitute for 18 F. New standardized solutions of each radionuclide were used to determine the response ratios while maintaining traceability to national standards. This work updates our previously published data from 2010. Methods: Following our previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The dose calibrator standard was assayed as if it were a patient dose. A conversion factor supplied by NIST allowed either 68 Ge or 18 F calibration settings to be used 18,19 for the measurement, and sites used 18 F settings to best represent clinical bias. A background radiation reading for the dose calibrator was recorded and subtracted from source assay.…”
Section: Calibration Measurementsmentioning
confidence: 99%
“…The dose calibrator standard was assayed as if it were a patient dose. A conversion factor supplied by NIST allowed either 68 Ge or 18 F calibration settings to be used 18,19 for the measurement, and sites used 18 F settings to best represent clinical bias. A background radiation reading for the dose calibrator was recorded and subtracted from source assay.…”
Section: Calibration Measurementsmentioning
confidence: 99%
“…The X-Cal independent cross-calibration kits were developed based on the traceable dose calibrator standards from RadQual, LLC., and the NIST (22, 23). In a previous study, using a larger prototype phantom with a 6 cm diameter, we found that bias in SUV measurements varied over time and between scanner sites (21).…”
Section: Discussionmentioning
confidence: 99%
“…Each source’s activity is known to within ±2.5% with a 95% confidence level (22, 23). The dose calibrator reference sources are directly traceable to National Institute of Standards and Technology (NIST) standards.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations